The Effect of Strengthening Knowledge in Pandemi Era on Community Behavior at Campus - Heny Sepduwiana; Elvira Junita; Rika Herawati; Andriana Andriana; Yuyun Bewelly Fahmi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2022)
The Covid-19 pandemic is a virus that is dangerous to humans. All segments of human life are disrupted, without exception education. Many countries have decided to close schools, colleges and universities, including Indonesia. The incidence of Covid 19 is increasing every day, the latest data from the Riau Provincial Health Office as of May 29, 2021, namely Pekanbaru 26,442 cases, Kampar 4054 cases, Palelawan 1776 cases, Indragiri Hulu 2675 cases, Indragiri Hilir 1492 cases, Dumai 5612 cases, Kap Meranti 826 cases, Bengkalis 3801 cases, Siak 4400 cases, Kuansing Singingi 2097 cases, Rokan Hilir, Rokan Hulu 1971 cases. This study aims to determine the effect of strengthening knowledge in the Pandemic era on community behavior on campus, which was collected using a questionnaire and analyzed by using the Chi Square test. ). Most of the respondents' behavior about COVID-19 was in the good category, namely 56 respondents (52.8%). Chi Square test on the knowledge and behavior of respondents showed the value of p value = 0.020 (p <0.05). From these results it can be concluded that there is a relationship between respondents' knowledge and COVID-19 prevention behavior in the community. Knowledge plays an important role in determining complete behavior because knowledge will form beliefs which then in perceiving reality, providing a basis for decision making and determining behavior towards specific object Keywords: Strengthening Knowldege, Community Behaviour, Pandemic Era